2022
DOI: 10.3390/vaccines10111958
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Attitudes toward Childhood Vaccines and COVID-19 Vaccines in a Turkish Pediatric Outpatient Population

Abstract: Vaccination hesitancy (VH) is an important public health issue. The determinants of parental decisions on whether to vaccinate their children are multidimensional and need to be carefully considered in the COVID-19 era. Our study aims to investigate the prevalence of VH among parents, parents’ use of social media, and their attitudes toward the COVID-19 vaccine upon vaccine refusal. Materials and methods: Our participants were the parents of children admitted to hospitals in three different cities in Turkey be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
1
12
0
1
Order By: Relevance
“…Over 10 billion doses have been delivered worldwide [ 7 ]. However, in low-income countries, the vaccination rate remains very low, and some people continue to doubt the benefits and effectiveness of vaccines [ 8 , 9 , 10 ]. Because of these issues, independent studies are specifically designed to offer evidence of the usefulness of vaccination programs.…”
Section: Introductionmentioning
confidence: 99%
“…Over 10 billion doses have been delivered worldwide [ 7 ]. However, in low-income countries, the vaccination rate remains very low, and some people continue to doubt the benefits and effectiveness of vaccines [ 8 , 9 , 10 ]. Because of these issues, independent studies are specifically designed to offer evidence of the usefulness of vaccination programs.…”
Section: Introductionmentioning
confidence: 99%
“…Five different assessment tools were employed in the included articles: Parent Attitudes About Childhood Vaccines (PACV), WHO Strategic Advisory Group of Experts Vaccine Hesitancy Scale (WHO SAGE VHS), a combination of both PACV and WHO SAGE VHS, Vaccine Confidence Index (VCI), and a self-structured questionnaire. The PACV questionnaire was applied in seven studies, encompassing a total of 5694 parents/caregivers in the countries of Italy [ 29 ], India [ 30 , 31 ], the USA [ 32 ], Canada [ 33 ], and Turkey [ 34 , 35 , 36 ]. The highest number of studies utilized the WHO SAGE VHS, with eight studies involving a sample size of 10,417 parents/caregivers from Pakistan [ 37 ], India [ 38 , 39 ], Cameroon [ 40 ], Ethiopia [ 41 ], China [ 42 ], France [ 43 ], and the Philippines [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Vaccine Confidence Index (VCI) was used in Brazil [ 51 ], involving 952 parents, of whom 352 were parents of children under 5 years of age. Out of the 32 countries examined in the study [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], 21 studies were carried out in countries categorized as high-income by the World Bank, 11 studies in upper-middle-income countries, 9 studies in lower-middle-income countries, and 1 study in a low-income country, specifically Ethiopia. Table 2 provides an overview of the characteristics of all the studies included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research studies conducted in Croatia also confirmed that the development speed was a crucial factor for the skepticism, both among the general public (Pavić et al, 2022; Bagić et al, 2022) and among healthcare workers (Miskulin et al, 2022). However, several research studies (Dombrádi et al, 2021; Durmaz et al, 2022; Meier et al, 2021; Olagoke et al, 2022; Romer et al, 2022; Ruiz & Bell, 2021) determined that there was a strong correlation between the acceptance of COVID-19 vaccines and other vaccine types, as well as that socio-demographic correlates of both types of vaccine hesitancy were similar. However, none of the studies was designed to deeply explore other types of determinants or possible differences in their mediation mechanisms.…”
Section: Introductionmentioning
confidence: 99%